2015
DOI: 10.1097/pcc.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Low Predictability of Three Different Noninvasive Methods to Determine Fluid Responsiveness in Critically Ill Children

Abstract: Dynamic preload variables such as stroke volume variation or respiratory variations in vena cava inferior diameter may not be useful for predicting fluid responsiveness in certain pediatric patient populations. Esophageal Doppler peak velocity was predictive of fluid responsiveness where a target value of more than 135,5 cm/s may be a signal to terminate further fluid challenges. This target value may be different in different age groups, as esophageal Doppler peak velocity varies with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 19 publications
2
49
0
4
Order By: Relevance
“…However, during spontaneous ventilation, lower RA pressure and uncontrolled, variable intrathoracic pressure changes with respiration may reduce the accuracy of IVC ultrasound to predict fluid responsiveness . The test characteristics of respiratory variation in IVC diameter in mechanically ventilated children are mixed, with reported AUROC values ranging from 0.37 to 0.85 . These studies all maintained tidal volumes of 8–10 mL/kg during IVC sonography, reducing one possible source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during spontaneous ventilation, lower RA pressure and uncontrolled, variable intrathoracic pressure changes with respiration may reduce the accuracy of IVC ultrasound to predict fluid responsiveness . The test characteristics of respiratory variation in IVC diameter in mechanically ventilated children are mixed, with reported AUROC values ranging from 0.37 to 0.85 . These studies all maintained tidal volumes of 8–10 mL/kg during IVC sonography, reducing one possible source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…29 The test characteristics of respiratory variation in IVC diameter in mechanically ventilated children are mixed, with reported AUROC values ranging from 0.37 to 0.85. [31][32][33] These studies all maintained tidal volumes of 8-10 mL/kg during IVC sonography, reducing one possible source of heterogeneity. However, all differed in their inclusion criteria, fluid bolus volume and content, their definition of fluid responsiveness and in their cut-off values for a positive index test.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased urine sodium levels are suggestive of a reduced effective circulating volume . Although IVCCI did not indicate a decreased intravascular volume in nine patients who were evaluated, several studies have shown that IVCCI is a poor predictor of central venous pressure or fluid responsiveness . Terai et al reported that IVIG‐resistant patients had higher vascular endothelial growth factor levels and gained more weight after IVIG than IVIG‐responsive patients .…”
Section: Discussionmentioning
confidence: 99%
“…18 Although IVCCI did not indicate a decreased intravascular volume in nine patients who were evaluated, several studies have shown that IVCCI is a poor predictor of central venous pressure or fluid responsiveness. 19,20 Terai et al reported that IVIG-resistant patients had higher vascular endothelial growth factor levels and gained more weight after IVIG than IVIG-responsive patients. 21 Vascular leakage might therefore cause intravascular volume depletion and decreased urine sodium levels, leading to a subsequent increase in total body water in KD.…”
Section: Discussionmentioning
confidence: 99%
“…Il faut noter que la plupart des paramètres dynamiques de précharge-dépendance n'ont été validés comme paramètres prédictifs de la réponse au remplissage vasculaire que chez des adultes ventilés (avec un volume courant >7 ml/kg) [38]. Chez l'enfant, seules les variations respiratoires du pic de vélocité du débit aortique semblent prédictives de cette réponse [39,40]. L'augmentation de l'index cardiaque après lever de jambe semble intéressante pour prédire la précharge dépendance mais mérite d'être confirmée [41].…”
Section: Sirsunclassified